Seinfeld. Season 4 [videorecording (DVD)] - Seinfeld, Jerry; David, Larry; Alexander, Jason, 1959-; Louis-Dreyfus, Julia; Richards, Michael, 1949- (Sony Pictures Home Entertainment, 2013)
The misadventures of neurotic New York stand-up comedian Jerry Seinfeld and his equally neurotic New York friends.